EXPLORING PRE-SERVICE TEACHERS’ PERCEPTION TOWARDS GENDER BIASED TEXTS IN EFL TEXTBOOK - Velya Primativa (Jurusan Sastra Indonesia, 2021)
In education, gender is a very serious issue that needs to be discussed, particularly in academic circles. Textbooks are the only open and inexpensive resource for education, they should have been a critical tool to identify better gender equity. The result of the research reveal that pre-service teachers still can not really comprehend the idea of gender bias and unable to notice that the texts are gendered.